O potrzebie elastyczności polskiego prawa podatkowego - Borszowski, Paweł (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
Article discusses a flexible tax law. The author advocates the use of the value of flexibility in tax law. The starting point are the determinants of the need to create a flexible tax law. Creating a flexible tax law requires consideration of the relationship between business transactions and tax law. Key considerations apply to grading flexible tax law.
Keywords: elastyczność; prawo podatkowe; determinanty; stopniowanie